Quest for the Grail? : Searching for Critical Thinking in Adult Education - Heather M. Boxler (Adult Education Research Conference, 2002)
The concept of critical thinking is explored from the perspective of an adult education graduate student. The paper argues that critical thinking, as presently constituted, lacks both clarity and depth. These problems need to be addressed before critical thinking can become viable and useful.